OPPORTUNITIES FOR IMPLEMENTING INVESTMENT PROJECTS ON THE BASIS OF PUBLIC-PRIVATE PARTNERSHIP IN AGRICULTURE - Yusufjonov Ravshanbek Rustamjon ugli (The Conference Hub, 2025)
Latest in years Uzbekistan in the economy public-private partnership (PPP) mechanisms current to be and development strategic from directions one as Especially in rural areas farm in the field state and private sector between cooperation reinforcement through efficiency increase, investment flow multiplication and innovative technologies current to grow opportunities expanding is going on.